PERANAN DAN KEDUDUKAN BADAN PENYELENGGARA JAMINAN PRODUK HALAL DALAM KELEMBAGAAN NEGARA - Amita Fayzia Handyani; Ninuk Wijiningsih (Reformasi Hukum Trisakti, 2023)
The executive, legislative, and judicial branches of government are examples of state institutions. The Halal Product Guarantee Agency, also known as BPJPH, was established by state institutions in Indonesia and is in charge of administering and disseminating halal certification. The formulation of the research problem is: what is the status of implementation regarding the granting of halal certification in Indonesia; and whether what BPJPH has done in implementing halal certification is in compliance with the applicable law. The solutions to these issues employ normative legal research methodologies, secondary data as the major source of information, some of which are descriptive in nature, can be qualitatively assessed, and deductive reasoning is used to derive conclusions. According to the study's findings, Indonesia's implementation of the issuance of halal certification complies with applicable law, and BPJPH's implementation of halal certification is still deficient, specifically during the halal certification period.